The levers of change project adoption in the organization of the developing countries: Case of the University of Mohamed Boudiaf at M’sila (Algeria) - عبد الرحمان, بوناب (جامعة المسيلة, 2021)
change levers are integral to implementing change in successful organizations, and the University of Mohamed boudiaf in the state of M’sila isn’t an exception. In this study, I relied on literature and studies concerned with change levers in organizational change management to figure out the intricacies of the change process inside the university. I sent an online survey to approximately 970 professors and managed to receive 85 responses. Said responses were analyzed using SPSS v22 to highlight the incentives the professors receive to adopt change inside the university and how many levers of change are implemented. Whilst many professors still have objections about how the change is implemented and their role and importance in the decision making-process, the study shows that the university implements change levers. In the study I used the Likert’s 7-point scale to deduce the results, and the study showed that the professors are neutral on 4 change levers, the first lever, a compelling case for change lever, had an arithmetic mean of 3.7804 , the second lever, challenging taken for granted, was 4.1020 . the 6th lever was 4.3765 and the 7th liver had 4.2147. they slightly agree on the implementation of 2 levers, the 4th lever, Symbolic management , which has an arithmetic mean of 4.9020 while the 5th lever, Power and political Systems, was 4.9686. they agree that the 3rd lever, changing operational procedures is implemented with a resulting arithmetic mean of 5.3137. Whilst the results vary slightly, there was no Lever of change agreed on as an unused lever. This conclusion is strongly supported by testing the 7 hypothesis dedicated to the effects of the change levers which resulted in the t being higher than Tabular t for all 7 levers which means that there is an effect.